Anonymous Aggregator Election and Data Aggregation in Wireless Sensor Networks - Tamás Holczer; Levente Buttyán (International Journal of Distributed Sensor Networks)
In mission critical cyber-physical systems, dependability is an important requirement at all layers of the system architecture. In this paper, we propose protocols that increase the dependability of wireless sensor networks, which are potentially useful building blocks in cyber-physical systems. More specifically, we propose two private aggregator node election protocols, a private data aggregation protocol, and a corresponding private query protocol for sensor networks that allow for secure in-network data aggregation by making it difficult for an adversary to identify and then physically disable the designated aggregator nodes. Our advanced protocols resist strong adversaries that can physically compromise some nodes.